Transport documents in carriage of goods by sea : international law and practice - Pejovic, Caslav (Abingdon, Oxon ; New York, NY : Routledge, 2020., 2020)
"Bringing a fresh, comparative approach to transport documents used in the carriage of goods by sea, this book covers bills of lading, sea waybills, ship's delivery orders, multimodal transport documents, and electronic transport documents. The book covers historic developments, current conventions, and thoughts for the future on these transport documents; and delves deeply into the legal issues concerning them. It represents a comprehensive compilation of case and statute law from around the world on this subject. In addition to English law, the book covers American, French, German, and Italian laws, as well as the laws of several East Asian jurisdictions (China, Japan, South Korea). Primarily, the book will be of use to maritime law scholars and students, and lawyers who deal with shipping. It may also be of interest to international traders, banks, and ship masters and officers"--
INTRODUCTION AND HISTORY -- DEFINITION AND FUNCTIONS OF BILL OF LADING -- ISSUANCE AND CONTENTS OF THE BILL OF LADING -- THE BILL OF LADING AS A RECEIPT -- THE BILL OF LADING AS A CONTRACT -- BILLS OF LADING UNDER TIME CHARTER -- BILL OF LADING AS DOCUMENT OF TITLE -- DELIVERY OF THE GOODS UNDER BILLS OF LADING -- THE ROLE OF THE BILL OF LADING IN INTERNATIONAL TRADE -- THE SEA WAYBILL -- SHIP'S DELIVERY ORDER -- MULTIMODAL TRANSPORT DOCUMENTS -- ELECTRONIC TRANSPORT DOCUMENTS -- FUTURE DIRECTIONS IN THE DEVELOPMENT OF TRANSPORT DOCUMENTS.
OCLC-licensed vendor bibliographic record.
Keywords: Bills of lading; Contracts, Maritime; LAW / General; LAW / International; LAW / Maritime